Household resource management practices of Kankanaey in La Union, Philippines - Tugelida, Nel Bryan C.; Chua, Consuelo T.; Bantang, Joanne R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Household resource management practices of household managers play a vital role in ensuring the welfare of the family. Likewise, reaching out to marginalized populace such as Indigenous People (IP) promotes cultural understanding and diversity. Thus, this research investigated the household resource management practices of Kankanaey household managers in the province of La Union, Philippines.
This research endeavor made use of a multi-method qualitative research design employing ethnography through in-depth Focus Group Discussions (FGDs), a case study through household immersion in a selected household, and a document review. The study involved a total of 30 household managers and 15 elders who were selected from six cultural barangays. To ensure the validity of the research instruments, the survey questionnaire and interview guide underwent validation by technical experts and were translated into the Ilokano dialect. Pilot testing was also conducted. The data collected from interviews, field observations, and document review were thematically analyzed using established procedures. The findings from the document review were then integrated into the review of related literature and discussed in relation to the study's results.
The study revealed that Kankanaey household managers have a set of household resource management practices towards money, time, and space which were grounded on their cultural beliefs and time-honored values; however, these are being influenced by formal education, Christianity, non-indigenous technologies, and non-indigenous practices through time. It was also found that although Kankanaey household managers utilized traditional technologies, they signify openness to use modern technologies in the management of their household resources. A framework in the management of household resources of Kankanaey household managers towards money, time, and space was crafted as an offshoot of this research endeavor to help various interested parties and stakeholders implement effective programs and activities for Kankanaey.
Dissertation
Bibliographical references (pages 222-238)
Keywords: Home economics -- Philippines; Kankanay (Philippine people) -- Home Economics -- Philippines